2014
DOI: 10.2135/cropsci2014.01.0063
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Affects the Germination of Forage Legume Seeds

Abstract: Temperature, in addition to moisture, oxygen, and light, plays an important role in seed germination. Early seedling emergence and stand establishment can be promoted by germination of seeds under a wide range of temperatures; therefore, it is desirable for commercial legume cultivars to germinate over a range of temperatures. The objective of this growth chamber experiment was to determine the effects of temperature on seed germination of seven annual warm‐season and 11 annual cool‐season legumes. Greatest ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…At the same time, the lowest germination percentage occurred in seeds exposed to the highest temperature (45 ± 2 • C), and was significantly lower than that of the lowest temperature tested in this study (5 ± 2 • C). This occurs because, according to Butler et al [44] very high temperatures (>40 • C) can affect the metabolic processes of the seeds and even damage them, halting embryonic growth, which can inactivate and kill them.…”
Section: Germinationmentioning
confidence: 99%
“…At the same time, the lowest germination percentage occurred in seeds exposed to the highest temperature (45 ± 2 • C), and was significantly lower than that of the lowest temperature tested in this study (5 ± 2 • C). This occurs because, according to Butler et al [44] very high temperatures (>40 • C) can affect the metabolic processes of the seeds and even damage them, halting embryonic growth, which can inactivate and kill them.…”
Section: Germinationmentioning
confidence: 99%
“…Using a previously described procedure, four replications of 100 seed of Asgrow AG5332, Progeny P5333RY, and the 10 F1 lines developed during experiment 1 were exposed to six levels of osmotic stress including 0.0, −0.1, −0.3, −0.5, −0.7, −0.9 [29]. The incubator was set at 25°C, which was the reported optimum temperature for the germination of soybean seed [30]. The plastic trays were vertically stacked inside the incubator and rearranged every 4 h to minimize the potential of small temperature fluctuations.…”
Section: Methodsmentioning
confidence: 99%
“…(Gresta et al, 2011), guar showed a much lower degree of hard seed, but a clearly higher threshold temperature for seed germination. Furthermore, compared to soybean and other warm-season legumes, guar exhibited a higher germination temperature; indeed, with respect to guar, some varieties of soybean were able to germinate at lower temperatures (10°C and 15°C), reaching up 54-62% germination at 10°C (Brar et al, 1991;Butler et al, 2014). On seven annual warm-season and eleven annual cool-season legumes, Butler et al (2014) found that germination of warm-season legumes tended to be maximized at 25°C, while the germination of cool-season legume was greatest from 10 to 25°C.…”
Section: Germination At Two Alternating Temperature Regimes (15/10 Anmentioning
confidence: 95%
“…Furthermore, compared to soybean and other warm-season legumes, guar exhibited a higher germination temperature; indeed, with respect to guar, some varieties of soybean were able to germinate at lower temperatures (10°C and 15°C), reaching up 54-62% germination at 10°C (Brar et al, 1991;Butler et al, 2014). On seven annual warm-season and eleven annual cool-season legumes, Butler et al (2014) found that germination of warm-season legumes tended to be maximized at 25°C, while the germination of cool-season legume was greatest from 10 to 25°C. The optimal temperature for both germination and seedling growth are adaptive traits to the environment of origin of the species (Motsa et al, 2015).…”
Section: Germination At Two Alternating Temperature Regimes (15/10 Anmentioning
confidence: 95%